HUBUNGAN PENGETAHUAN, POLA MAKAN, DAN AKTIVITAS FISIK DENGAN KEJADIAN GIZI LEBIH PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS SUMATERA UTARA TAHUN 2015 - Chelsea Andini Marpaung; Zulhaida Lubis; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Nutrition problem has been the main of health problem in Indonesia. In the globalization era, Indonesia faces a double nutrition problems, they are the problem of malnutrition and over nutrition. As a developing country, cases of malnutrition have long existed in Indonesia, but with diet changing, economic progress, and lack of nutritional knowledge has made the increasing number of overnutrition in Indonesia. In FKM USU, student having overnutrition because of diet, knowledge dan physical activity. The aim of the research was looking for the relation among knowledge, diet, physical activity, and overnutrition on students of FKM USU. The design of research used a cross sectional method for looking the relation knowledge, diet, and physical activity on the incidence of overnutrition students of the Public Health Faculty, University of North Sumatera. The population in this study is all students in semester 3 until 7 at FKM USU as many as 1978 people, with a sample of 108 people. Results of research by chi-square test showed that the variables diet consists of the types of food that seen from the completeness food and number of meals as seen from the adequacy of fat significantly to the incidence of obesity related and nutritional status, p = 0.001 <0.005 and physical activity with p = 0.001 <0.005. Factors related to the occurrence of nutrition in students of FKM USU  the diet that is the type of food which is viewed by the completeness and adequacy fat meal and physical activity. FKM is advisable for adding some lecture meterials and having some discussion about overnutrition to increase student warning about it. Keywords: Diet, Knowledge, Overnutrition, Physical Activity